From Recording to Reporting: Digital Accounting Practices in Msmes in Batam City - Martius (Jurnal Dialektika: Jurnal Ilmu Sosial, 2026)
This study explores how micro, small, and medium enterprises (MSMEs) in Batam City transform digital transaction recording into financial reporting. Drawing on TOE, UTAUT, and practice theory, digital accounting is treated as routines shaped by capability, role allocation, and external demands. Using a qualitative case-study design, data were gathered through semi-structured interviews, limited observation, and document review, then analyzed thematically. Results indicate that digital tools are adopted mainly for pragmatic needs (sales and cash recap), while the process often stalls at input and summary stages. Data validation and periodic statement preparation are not embedded as stable routines, so reporting is typically incidental for loans, taxes, or partner requests. Hybrid practices (apps alongside manual notes) and uneven accounting literacy constrain the production of consistent income statements and balance sheets. The study maps key bottlenecks and realistic enabling conditions for moving from recording to reporting